“The Clash of Civilization”: A Prognosis of the Future or the Lure of the Past - Taufik Abdullah (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1998)
This article is seen as one response to the Clash of Civilization thesis and wanted to test the accuracy of the analysis of Samuel Huntington back in the context of the uniqueness of Islam in Indonesia.The story begins when Samuel P. Huntington - the famous political scientist from the highly prestigious Harvard Uinversity and a citizen of the most powerful nation - writes an article, entitled